2010
DOI: 10.1021/bm100854a
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made Conjugated Polymer Nanoparticles for Multicolor and Multiphoton Cell Imaging

Abstract: Sonogashira coupling of dibromo- and diethynyl-substituted benzenes and fluorenes in aqueous mini-emulsion afforded colloidally stable dispersions of highly fluorescent 60-120 nm particles of poly(arylene ethynylene)s of molecular weights M(n) 4 × 10(4)-2 × 10(5) g mol(-1) with solids contents up to 15 wt %. By covalent incorporation of diethynyl pyrrolo-pyrrole or diethynyl fluorenone in the mini-emulsion polymerization the emission color of these photostable nanoparticles can be tuned from blue (λ(em max) 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 31 publications
1
103
0
5
Order By: Relevance
“…In order to meet the needs of multiplexed biological imaging, CPNs have also been made for multicolor cell imaging. 60-120 nm particles of highly fluorescent poly(arylene ethynylene)s that were copolymerized with dibromo-substituted fluorenone showed emissions ranging from blue to orange color [24]. Fluorescent quantum yields increased with dye incorporation from 44% to over 60% and photostability studies showed a high tolerance of the CPNs to bleaching; after 500s of irradiation, there was no decrease in fluorescence.…”
Section: Imaging With Cpnsmentioning
confidence: 99%
“…In order to meet the needs of multiplexed biological imaging, CPNs have also been made for multicolor cell imaging. 60-120 nm particles of highly fluorescent poly(arylene ethynylene)s that were copolymerized with dibromo-substituted fluorenone showed emissions ranging from blue to orange color [24]. Fluorescent quantum yields increased with dye incorporation from 44% to over 60% and photostability studies showed a high tolerance of the CPNs to bleaching; after 500s of irradiation, there was no decrease in fluorescence.…”
Section: Imaging With Cpnsmentioning
confidence: 99%
“…[40][41][42][43][44] Es gab beachtliche Bemühungen, vielseitige halbleitende Polymernanopartikel (eine kleine Untergruppe davon sind die P-Punkte) zu erzeugen, ihre Eigenschaften und Funktionen einzustellen und deren Leistung für biomedizinische Untersuchungen zu verbessern. Die Forschungsbemühungen umfassen die Nutzung neuer Herstellungsverfahren, [45,46,69,70,72] die Untersuchung von NanopartikelBildungsmechanismen, [120,121] Sondierung der Photophysik der Nanopartikel, [47,49,54,122,123] Charakterisierung der Fluoreszenzleistung, [48,51,56,58] Abstimmung der Emissionsfarbe, [47,49,71,89] das Manipulieren der Partikeloberflä-che, [56-58, 64-66, 98, 102] die Verkapselung von anorganischen Materialien, [96,97,99,104,105] Entwicklung von Nanopartikelsensoren, [52,59,60,62,74,77] die Bildung von zellulären Strukturen, [56,57,[63][64][65][66] sowie das In-vivo-"Targeting" bei kleinen Tieren. [58,…”
Section: Von Konjugierten Polyelektrolyt-biosensoren Zu Hydrophoben Punclassified
“…[130,131] Erst kürzlich wurde dieser Ansatz auf fluoreszierende halbleitende Polymere ausgeweitet, um daraus Nanopartikel herzustellen. [69][70][71]132] [94,95] allerdings waren die Partikel etwa 250 nm groß und wiesen eine relativ geringe Fluorophorkonzentration auf (ca. 1 Gew.-%).…”
Section: Herstellungsverfahrenunclassified
“…Recently, an excellent study by Kuehne et al [111] demonstrated that the highly monodisperse nanoparticles of PF-01f (PFO-co-F2/6), PF-04a (F8BT) and PF-15 could be prepared via Suzuki-Miyaura dispersion polymerization using a surfactant mixture of poly(1-vinylpyrrolidone-co-vinyl acetate), Triton X-45 and 1-propanol, which these monodisperse particles readily self-assemble into photonic crystals that exhibit a pronounced photonic stopgap. Nanoparticles of PF-07 and PF-09a-d have been reported via Knoevenagel and Sonogashira coupling emulsion polymerization, respectively [182][183][184]. Re-precipitation is an alternative method for obtaining hydrophobic nanoparticles, which was first employed for producing PF-based nanoparticles, as reported by McNeill and co-workers [191].…”
Section: Introductionmentioning
confidence: 98%
“…PF-CPNs can be further functionalized by cross-linking, blending, encapsulation and surface modification (figure 4), which have more advantages over the precursor nanoparticles for [104]; PF-01a and 06 from [177]; PF-01e and 15 from [111]; PF-07 from [182]; PF-09a, 09b and 9c from [183,184]; PF-04a from [111,185]; PF-04c from [186]; PF-04e, 08a and 08b from [187,188]; PF-10a from [189]; PF-01b from [190]; PF-01c from [191]; PF-03c from [192]; PF-03d and 3e from [193]; PF-04b from [194]; PF-10b from [195]; PF-16 from [176]; PF-17a from [180]; PF-17b from [173]; PF-04a and PF-05 or PF-01f and PF-02 from [163]; PF-3a, 3b and 12b from [196,197]; PF-11 from [198]; PF-12a from [199]; PF-18 from [200]; PF-13 from [201]; and PF-14b-14e from [202]. (Online version in colour.)…”
Section: Introductionmentioning
confidence: 99%